2020
DOI: 10.1111/zph.12759
|View full text |Cite
|
Sign up to set email alerts
|

Perception of health risks in Lao market vendors

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…About 40% of respondents expressed fear ratings of EVD of greater or equal to 7 out of 10. There was no professional difference in rating of fear (categories: Doctor–Nurse–Other Health/Paramedical–Non-Medical Health Workers— P > 0.05) None None Acceptable Olowookere et al 2015 [ 80 ] Nigeria Ebola virus disease Health professionals: clinical and non-clinical health workers Cross-sectional study Quantitative data Self-administered questionnaire Consider self to be at risk: 39% agree, 42.8% disagree, 18.2% undecided Consider health workers prone to EVD: 75.8% agree, 12.7% disagree, 11.5% undecided None None Ozioko et al 2018 [ 56 ] Nigeria Zoonotic infections General adult population: bushmeat traders and hunters Cross-sectional study Quantitative data Interviewer-administered questionnaire Bushmeat hunters: yes 47.1%, no 52.9% Bushmeat traders: yes 71.4% no 28.6% P = 0.36 None None Good Philavong et al 2020 [ 65 ] Lao Zoonotic infections General adult population: market vendors (vegetable, livestock and bushmeat) Cross-sectional study Quantitative data Interviewer-administered questionnaire 72%of vendors considered that their job did not put their health at risk, highest among bushmeat vendors compared to vegetable or livestock vendors The proportion of vendors who reported that they had “no risk” was higher when asked about their personal risk compared to when they were asked about risk in general, and this was consistent for vegetable vendors (chi-square test, P < 0.001), livestock meat vendors (chi-square test, P = 0.055) and bushmeat vendors (chi-square test, P = 0.0037) Number of education years Belief in safety and quality of products sold None Good Rizwan et al 2020 [ 42 ] Pakistan COVID-19 …”
Section: Resultsmentioning
confidence: 99%
“…About 40% of respondents expressed fear ratings of EVD of greater or equal to 7 out of 10. There was no professional difference in rating of fear (categories: Doctor–Nurse–Other Health/Paramedical–Non-Medical Health Workers— P > 0.05) None None Acceptable Olowookere et al 2015 [ 80 ] Nigeria Ebola virus disease Health professionals: clinical and non-clinical health workers Cross-sectional study Quantitative data Self-administered questionnaire Consider self to be at risk: 39% agree, 42.8% disagree, 18.2% undecided Consider health workers prone to EVD: 75.8% agree, 12.7% disagree, 11.5% undecided None None Ozioko et al 2018 [ 56 ] Nigeria Zoonotic infections General adult population: bushmeat traders and hunters Cross-sectional study Quantitative data Interviewer-administered questionnaire Bushmeat hunters: yes 47.1%, no 52.9% Bushmeat traders: yes 71.4% no 28.6% P = 0.36 None None Good Philavong et al 2020 [ 65 ] Lao Zoonotic infections General adult population: market vendors (vegetable, livestock and bushmeat) Cross-sectional study Quantitative data Interviewer-administered questionnaire 72%of vendors considered that their job did not put their health at risk, highest among bushmeat vendors compared to vegetable or livestock vendors The proportion of vendors who reported that they had “no risk” was higher when asked about their personal risk compared to when they were asked about risk in general, and this was consistent for vegetable vendors (chi-square test, P < 0.001), livestock meat vendors (chi-square test, P = 0.055) and bushmeat vendors (chi-square test, P = 0.0037) Number of education years Belief in safety and quality of products sold None Good Rizwan et al 2020 [ 42 ] Pakistan COVID-19 …”
Section: Resultsmentioning
confidence: 99%
“…Although a prior infection with SARS-CoV-1, the causative agent of SARS, may confer cross-reactivity to SARS-CoV-2 due to neutralizing activity of antibodies against the highly homologous Receptor Binding Domain [ 43 , 44 ], such instances are probably insignificant in Lao PDR [45] . It is nevertheless possible that exposure to other coronaviruses occurs in Lao PDR given the frequent trade in bush meat and low biosafety awareness [46] . Indeed, it has been shown that bats and rodents from Lao PDR and bordering countries can be infected with a diverse array of alpha- and beta- coronaviruses including SARS-CoV-2–like viruses [47] , [48] , [49] , [50] , [51] .…”
Section: Discussionmentioning
confidence: 99%
“…The sale of wildlife products to consumers, certainly of illegal products, is often conducted through informal networks [63]. However, the sale of wildlife products through commercial bushmeat markets and live animal markets is prevalent, and this type of sale is documented at least to some extent [35,64,65].…”
Section: Phase 3salementioning
confidence: 99%
“…Local awareness of zoonotic diseases can also contribute to reducing bushmeat hunting rates. While conservation-education programmes are unlikely to impact local hunting and wildlife use due to the cultural and religious significance of bushmeat, health-risk education has the potential to minimise hunting rates of species, like nonhuman primates, that pose a particular risk to human health [53,63,70,141]. Still, Friant et al [76] found that individuals did protect themselves against infection despite being aware of zoonotic disease risks.…”
Section: Local Community Support Education and Involvementmentioning
confidence: 99%